Vocational Development Initiatives for Youth Empowerment: Case of the Nigeria Secondary Schools’ Curriculum - Peter, Ogundola Ilesanmi; Gabriel, Agboola Babajide; Kehinde, Usman Asipita (Mediterranean Journal of Social Sciences, 2020)
The study was carried out to evaluate the Vocational Development initiatives of the Nigerian secondary education curricula introduced by the National Education Research and Development Council (NERDC). Five research questions were formulated to guide the study. Descriptive survey design was adopted. The study was carried out in Kogi State. Sample for the study was 220 respondents made up of 102 male and 118 female senior secondary school students offering trade subjects. A structured questionnaire titled Vocational Development Initiatives for Youth Empowerment (VDIYE) questionnaire was developed for data collection. The questionnaire was face and content validated by three vocational education experts. The reliability of the questionnaire was determined using the test re-test reliability method which yielded a co-efficient of 0.72. The data collected were analyzed using descriptive statistics. Based on the data collected and analyzed, it was observed that majority of respondents view trade subjects as desirable and that it prepares them adequately for future vocational career choice among other findings. Recommendations were thereafter made on ways to improve on trade subjects. This is in order to achieve the desired objectives of making secondary school graduates to be job creators and also reduce unemployment.